Children's Drawings: Strokes, Colors and Stories that Make Us Reflect and Learn - Amalia Molina-Jiménez (Universidad Nacional, Costa Rica, 2015)
The purpose of this participatory action research is to evidence the drawing evolution of five boys and five girls, ages 5 and 6, regarding the construction of the human body, the use of color, and the location of objects in space over a six-month period.  Drawing was the way in which children visually expressed their feelings, thoughts, desires, emotions, and interests.  This let the teacher-researcher build new learning, which, together with the one constructed by the children, broke the paradigm and transformed the art teacher's role in the classroom, from the children's perspective.  This helped the teacher realize that it is possible to get rid of prejudices and the adult point of view that frequently restricts children in what they are and what they do.